Evaluation of Total Plate Count (TPC) on Eating Utensils of Lontong Kupang Vendors in Surabaya: A Study on Health and Hygiene - Amelya Dewi Laskar Pratiwi; Rusmiati; Sri Anggraeni; Narwati; Dya Candra Maulawati Sani Putranti (Jurnal Higiene Sanitasi, 2024)
Foodborne diseases can be influenced by many factors. One of the causes of foodborne diseases is the contact of food with utensils containing microorganisms. The total plate count on the utensils used by lontong kupang vendors in Surabaya exceeds the standard quality, due to only having one sink for washing utensils and the open storage of these utensils. The aim of this study is to determine the Total Plate Count of eating utensils used by lontong kupang vendors in Surabaya in 2024. This is a descriptive study with a cross-sectional approach. The objects used in the study are eight lontong kupang vendor stands. The research sample consists of 16 utensils, including plates and spoons, tested for Total Plate Count, and clean water tested in the laboratory for microbiological parameters, including total coliform bacteria and E. coli. Data analysis is conducted descriptively based on laboratory test results and observation/checklist sheets. The study results show that the Total Plate Count on utensils at 56% of the eight stands met the requirements. The physical quality of clean water met the standards, but microbiologically, the total coliform and E. coli parameters did not meet the standards. The washing facilities were rated as adequate (60%). The cleanliness of eating utensils at the eight lontong kupang stands was categorized as good (75%). The study concludes that the Total Plate Count of eating utensils used by lontong kupang vendors in Surabaya does not meet the requirements. It is recommended that lontong kupang vendors store their utensils in closed containers, and the management should regularly drain water tanks and check the water distribution system